Parameter determination for a computer simulation model of a diver and a springboard - Yeadon, M. R.; Kong, P. W.; King, M. A. (Journal of Applied Biomechanics, 2006)
This study used kinematic data on springboard diving performances to estimate viscoelastic parameters of a planar model of a springboard and diver with wobbling masses in the trunk, thigh, and calf segments and spring dampers acting at the heel, ball, and toe of the foot segment. A subject-specific angle-driven eightsegment model was used with an optimization algorithm to determine viscoelastic parameter values by matching simulations to four diving performances. Using the parameters determined from the matching of a single dive in a simulation of another dive resulted in up to 31% difference between simulation and performance, indicating the danger of using too small a set of kinematic data. However, using four dives in a combined matching process to obtain a common set of parameters resulted in a mean difference of 8.6%. Because these four dives included very different rotational requirements, it is anticipated that the combined parameter set can be used with other dives from these two groups.